UMP's six entries all won medals including two gold medals at Water Malaysia Exhibition and Competition 2013 - Noor Syahidah, Sabran (Penerbit UMP, 2013)

(untitled)
Universiti Malaysia Pahang (UMP) took part in the Water Malaysia Exhibition and Competition 2013 held at Kuala Lumpur Convention Centre on April 23-25, 2013.